Cuaderno de trabajo de ciencias naturales con técnicas activas para potenciar la inteligencia naturalista en el octavo año de educación básica. - Pepinoza Caicedo, Liliana Alexandra (2013)
The human being is possessed of eight types of intelligences that develop in each one on a different scale and in different ways. Naturalist intelligence is a competition to gain insight into the surrounding environment, through exploration based on interest and enthusiasm who want to expand their knowledge, taking advantage of every opportunity that is presented to observe, analyze, interact with plants, animals and objects can promote their care and protection. Let the person who has mostly developed this intelligence search strategies to understand the features, functions and actions of every being. Naturalist intelligence shows interest in biology, botany, zoology, forestry, etc. ,Ie everything that has to do with nature and its cycles in an effort to discover their interconnections, relationships between living biotic and abiotic elements.